Social and Spiritual Meanings in the Cabur Bulung Tradition of Karo Ethnicity: An Anthropological Perspective - Simangunsong, Cladeo; Ginting, Natalia; Syahfitri, Rindani; Panjaitan, Rinaldi; Syafitri, Astrid; Arianto, Tomi (Yayasan Tri Edukasi Ilmiah, 2024)
This research aims to analyze the social and spiritual meanings in the Cabur Bulung tradition of the Karo Ethnicity, as well as to understand its role and function in the context of the social and spiritual life of the Karo community. Based on Geertz's (1973) cultural theory, which suggests the importance of symbols and meanings in the interpretation of a community's social life, this research adopts an anthropological approach with qualitative methods. Techniques used include observation, in-depth interviews, and literature studies to explore the meaning dimensions of the Cabur Bulung tradition. The results show that the Cabur Bulung tradition has two main dimensions, namely social and spiritual. Socially, this tradition functions as a means to strengthen relationships between community members, strengthen Karo ethnic identity, and demonstrate the value of solidarity and togetherness in social life. On the other hand, the spiritual dimension of this tradition reveals the Karo people's efforts to communicate with the spirits of ancestors, ask for healing blessings, and maintain balance with the universe. The symbols contained in the Cabur Bulung procession contain deep social and religious values, describing human relationships with the spiritual world and nature. This research provides an understanding of the Cabur Bulung tradition as an inseparable part of Karo ethnic culture, and reveals its role in shaping social structures, cultural identity and practices. he spirituality of the Karo people. Thus, this tradition is not only a ritual, but also a reflection of life that involves harmonious social and spiritual relationships between humans, communities and the spirit world.